Role of conflict management in preventing burnout due to work conflicts among nurses : A qualitative study - Nisa, Neng Lina Rohmatun; Sutresna, Iyos; Ridwan, Heri (Lentera Perawat, 2026)
Background: Workplace conflict is an inevitable phenomenon in nursing practice and, when unresolved, may contribute to burnout among nurses, particularly in primary healthcare settings. Burnout negatively affects nurses’ well-being, work performance, and quality of care, highlighting the importance of effective conflict management strategies at the organizational level. Objective: This study aimed to explore nurses’ experiences of workplace conflict and to examine the role of conflict management in preventing burnout among nurses at Puskesmas Cimalaka. Methods: A qualitative study with a phenomenological approach was conducted. Six participants, consisting of four staff nurses and two nurse-in-charge personnel, were recruited using snowball sampling. Data were collected through in-depth interviews and contextual observations. Verbatim transcripts were analyzed thematically to identify patterns, themes, and meanings related to workplace conflict, burnout, and conflict resolution strategies. Results: All participants reported experiencing workplace conflict, which was generally mild and work-related, including miscommunication, task distribution issues, tardiness, and scheduling conflicts. Five participants experienced signs and symptoms of burnout, primarily emotional exhaustion and temporary psychological strain. Conflict resolution involved peer-assisted approaches and supervisor-mediated interventions. Effective strategies identified were compromise and collaboration, which contributed to timely conflict resolution, improved communication, a more comfortable work environment, increased motivation, perceptions of fairness, and reduced risk of burnout. Conclusion: Workplace conflict among nurses at Puskesmas Cimalaka is common but manageable. Proactive, fair, and collaborative conflict management strategies play a critical role in mitigating the risk of burnout. Strengthening institutional conflict management mechanisms and addressing structural factors such as workload are essential to sustain nurses’ well-being in primary healthcare settings